A reusable material with high performance for removing NO at room temperature: performance, mechanism and kinetics. Issue 10 (5th January 2016) - Lu, Pei; Xing, Yi; Li, Caiting; Qing, Renpeng; Su, Wei; Liu, Nian
Abstract : Removing NO from the air with a reusable material at room temperature is challenging. Abstract : Removing NO from the air with a reusable material at room temperature is challenging. In this study, a series of urea–MnO x /ACF and urea– x (CeO2 –(1 − x )MnO2 )/ACF materials were prepared and used for removing NO at room temperature. The results showed that 10% urea–8% (0.5CeO2 –0.5MnO2 )/ACF yielded the highest NO conversion, which showed an NO conversion ratio above 90% with 1000 ppm NO in the initial mixed gases. Moreover, the NO conversion exceeded 98% when the NO concentration was 100 ppm in the initial mixed gases. More importantly, 10% urea–8% (0.5CeO2 –0.5MnO2 )/ACF was stable even after it was regenerated by reloading with urea, demonstrating that the material could be easily reused and its high performance was maintained. Finally, the mechanism and kinetics of the NO removal was discussed.